Effects of Handling Stress of Gilts During Gestation on Embryonic Survival - Srinoy Chumkam; J.T. Yu; Chanvit Vajrabukkal (Agriculture and Natural Resources, 1993)
In the study of the effects of handling stress on reproductive performance of gilts, 18 gilts were allocated to either stress (blood collection) or control (no blood collection) treatments. They were housed in the same building. On day 20-22 after insemination all the gilts were slaughtered and it had been found that the number of corpora lutea, corpora lutea size and embryonic mortality were not significantly difference but the rectal temperature was found to be significantly difference. There was a marked drop of rectal temperature over number of days after they had been inseminated. It was concluded that in more severe environmental conditions, handling of early pregnant gilts should be treated with great care.